A New Hope for African Women: Overview of Africa’s Protocol on Women’s Rights (Nordic Journal of African Studies, 2004)
There can be no doubt today that the human rights of women and of the girl-child are an inalienable, integral and indivisible part of universal human rights. However, for long African women have been suffering several human rights abuses, both in the private and public spheres. For instance, denial of inheritance rights and exclusion from participation in the governance of their countries. Remarkably, this is so despite the existence of several international instruments on the rights of women, including the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW), of which most African countries are States Parties. This was the situation when the Protocol to the African Charter on Human and Peoples’ Rights on the Rights of Women was adopted recently at Maputo, Mozambique. This article seeks to provide an overview of this important Protocol, and to show the new hope it holds for African women.